2016
DOI: 10.1016/j.schres.2015.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Intact implicit processing of facial threat cues in schizophrenia

Abstract: An emerging body of research suggests that people with schizophrenia retain the ability to implicitly perceive facial affect, despite well-documented difficulty explicitly identifying emotional expressions. It remains unclear, however, whether such functional implicit processing extends beyond emotion to other socially relevant facial cues. Here, we constructed two novel versions of the Affect Misattribution Procedure, a paradigm in which affective responses to primes are projected onto neutral targets. The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 54 publications
1
15
2
3
Order By: Relevance
“…In SZ, when comparing both implicit and explicit processing, implicit emotion processing seems less affected [46]. These results suggest that emotional faces are correctly perceived by patients with SZ at non-awareness level or at early processing but may be biased at higher top-down processing levels [47][48][49]. Nevertheless, a study using event-related potentials found impaired bottom-up processing rather than top-down dysfunction for facial emotion recognition in SZ [50].…”
Section: Behavioural Correlates Of Facial Emotion Processingmentioning
confidence: 81%
“…In SZ, when comparing both implicit and explicit processing, implicit emotion processing seems less affected [46]. These results suggest that emotional faces are correctly perceived by patients with SZ at non-awareness level or at early processing but may be biased at higher top-down processing levels [47][48][49]. Nevertheless, a study using event-related potentials found impaired bottom-up processing rather than top-down dysfunction for facial emotion recognition in SZ [50].…”
Section: Behavioural Correlates Of Facial Emotion Processingmentioning
confidence: 81%
“…De nombreuses études retrouvent des déficits de la cognition sociale chez les patients schizophrènes (1,2,4,7,28,45,49,58,(85)(86)(87)(88)(89)(90)(91)(92)(93)(94) et ce dans les différents domaines qui la composent : a. Les perceptions sociales : Les patient ont des difficultés à reconnaitre les émotions sur les visages (4,11,49,(85)(86)(87)95,96). Ils auraient tendance à repérer des indices de menaces faciaux là où il n'y en a pas (96). Cependant ils auraient beaucoup de mal à percevoir les émotions négatives et la peur sur les visages.…”
Section: Vii) La Cognition Socialeunclassified
“…(55) Cependant, d'après certaines études, leurs difficultés dans le traitement des informations faciales seraient surtout liées à leur capacité à utiliser ces informations. En effet ils garderaient une capacité intacte au traitement implicite de ces informations (96).…”
Section: Vii) La Cognition Socialeunclassified
See 1 more Smart Citation
“…However, some studies have reported preserved perceptual and emotional processing of facial expressions in schizophrenia [18]. Behavioural studies have demonstrated that emotional facial expressions presented under a priming procedure [19][20][21] or continuous flash suppression [22] can bias subjective evaluation of subsequent neutral stimuli in schizophrenia and control groups. Furthermore, threatening faces enhanced the performance of a delayed matching task [23], and such expressions interfered with a gender discrimination task in schizophrenia and control groups [24].…”
Section: Introductionmentioning
confidence: 99%